Accuracy and image quality of wide-detector revolution CT angiography combined with prospective ECG-triggered CT angiography in the diagnosis of congenital aortic arch anomalies in Chinese children - Xiao, Hui-Jun; Zhan, A-Lai; Huang, Qing-Wen; Huang, Rui-Gang; Lin, Wei-Hua (Frontiers in Pediatrics, 2022)
Objective: To explore the accuracy and image quality of wide-detector revolution CT angiography combined with prospective ECG-triggered CT angiography in the diagnosis of congenital aortic arch anomalies in Chinese children. Methods: From January 2020 to July 2022, the clinical data of 57 children with congenital aortic arch anomalies confirmed by surgery were collected. All patients underwent CT angiography (CTA) with Revolution CT and transthoracic echocardiography (TTE) before the operation. The accuracy of CTA and TTE in the diagnosis of aortic arch anomalies was compared with the surgical results. Result: The diagnostic sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of CTA and TTE for congenital aortic arch anomalies (including intracardiac and extracardiac structural abnormalities) were 92.2% and 85.5%, 99.4%, and 99.1%, 97.4% and 95.6%, 98.1% and 96.9%, and 97.2% and 95.2%, respectively. Regarding extracardiac structural malformations, the sensitivity of CTA was 100%, whereas that of TTE was 78.6% (P<0.001). Regarding intracardiac structural malformations, the sensitivity of CTA was 84.5%, whereas that of TTE was 92.5% (P<0.001). Regarding satisfaction with the images in aortic arch anomalies, surgeons noted that the CTA images were more useful for diagnosis and operation planning compared with TTE. Conclusion: Wide-detector revolution CT angiography combined with prospective ECG triggering can be routinely used to assess congenital aortic arch anomalies, providing adequate image quality and high diagnostic accuracy. However, limitations in the identification of intracardiac structural abnormalities are noted.